Transfer sequences involving persons with dementia: Instrumental tasks as opportunities for conversation. (7th January 2020) - Kristiansen, Elisabeth; Andersen, Elisabeth; Rasmussen, Gitte
Abstract : This article analyzes a series of sequences taking place in the common room of a Danish dementia care unit in which food or drink is given to a resident with dementia. Giving something to a resident, such as food or drink, constitutes a recurring common activity for care staff and residents and thus also provides an opportunity for talk between the resident with dementia and the care staff. However, in many cases, rather than engaging residents in talk in connection with e.g. offering of food or drink, care staff resorts to so-called 'care speak' (Ward, Vass, Aggarwal, Garfield, and Cybyk, 2008), i.e. neither requiring nor eliciting input from residents when accomplishing the transfer of food or drink to the resident. This article aims to show in what ways the transferrers' interactional methods influence the opportunities for participation for the resident. The analyses show first that sequences without a preceding offer sequence are accompanied by a verbal narration of the transfer of the object during the transferring action itself, thus presuming compliance from the recipient. Second, they show that sequences in which the transfer of the object is preceded by offer sequences seek the recipient's acceptance before carrying out the transfer. Thereby, transfer sequences preceded by offer sequences provide participants with sequential opportunities for willingly engaging in an upcoming activity as an individual with the capacity of making choices while transfer sequences without offer sequences do not. However, as we show, the organization of transfer sequences depends not only on verbal contributions but also on participants' embodied conduct.